Rabies in Children (An Eleven Years Retrospective Study in Medan) - Rafita Ramayati; Rusdidjas Rusdidjas; Helena Siregar (Indonesian Pediatric Society, 1982)
At the Department of Child Health Medical School University of NorthSumatera/Dr. Pirngadi Hospital Medan, a retrospective study for analysis onRabies in Children from 1977 - 1980 had been carried out. We found 29cases consisting of 23 males arul 6 females. The highest incidence was between 6 - 12 years. All was bitten by dogs.Lower limbs were the most common site of dog bite. Twenty of the 29cases were derived from Medan Munic TJ!e. All of the cases did not receivedpost